Pendidikan Karakter dan Moderasi Beragama Dalam Konteks Ajaran Niti Sastra - Ni Nyoman Rahmawati; I Made Sadiana (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
Abstrak This article aims to provide solutions to overcome the problems of radicalism and intimidation that are increasingly prevalent in society in the name of religion There are three problems in this article, namely: How does a multicultural and plural society practice religious moderation in Indonesia, how is religious moderation taught in Niti Sastra and the importance of religious moderation education in a plural society. In analysing the problem, library research method is used. The results obtained are: (1). The practice of religious moderation in Indonesia is reflected in several moments of religious rituals such as the celebration of Eid al-Fitr, Christmas, and Nyepi, as well as incidental activities such as grief and marriage. (2). The value of religious moderation in Niti Sastra is reflected in various character education that is emphasised to be a good leader such as mutual respect, appreciation (3) Religious moderation in plural societies is very important to be applied to overcome the distortion of community morality values, an important key to the unity and integrity of the Indonesian nation, and to preserve the continuity of traditions.